Combined morphologic-metabolic biomarkers from [18F]FDG-PET/CT stratify prognostic groups in low-risk NSCLC - Deininger, Katharina; Raacke, Joel Niclas; Yousefzadeh-Nowshahr, Elham; Kropf-Sanchen, Cornelia; Muehling, Bernd; Beer, Meinrad; Glatting, Gerhard; Beer, Ambros J.; Thaiss, Wolfgang (Nuklearmedizin - NuclearMedicine, 2023)
Aim The aim of this study was to derive prognostic parameters from 2-[18F]fluoro-2-deoxy-D-glucose ([18F]FDG-PET/CT) in patients with low-risk NSCLC and determine their prognostic value.Methods 81 (21 female, mean age 66 a) therapy-naive patients that underwent [18F]FDG-PET/CT before histologic confirmation of NSCLC with stadium I and II between 2008–2016 were included. A mean follow-up time of 58 months (13–176), overall and progression free survival (OS, PFS) were registered. A volume of interest for the primary tumor was defined on PET and CT images. Parameters SUVmax, PET-solidity, PET-circularity, and CT-volume were analyzed. To evaluate the prognostic value of each parameter for OS, a minimum p-value approach was used to define cutoff values, survival analysis, and log-rank tests were performed, including subgroup analysis for combinations of parameters.Results Mean OS was 58±28 months. Poor OS was associated with a tumor CT-volume >14.3 cm3 (p=0.02, HR=7.0, CI 2.7–17.7), higher SUVmax values >12.2 (p=0.003; HR=3.0, CI 1.3–6.7) and PET-solidity >0.919 (p=0.004; HR=3.0, CI 1.0–8.9). Combined parameter analysis revealed worse prognosis in larger volume/high SUVmax tumors compared to larger volume/lower SUVmax (p=0.028; HR=2.5, CI 1.1–5.5), high PET-solidity/low volume (p=0.01; HR=2.4, CI 0.8–6.6) and low SUVmax/high PET-solidity (p=0.02, HR=4.0, CI 0.8–19.0).Conclusion Even in this group of low-risk NSCLC patients, we identified a subgroup with a significantly worse prognosis by combining morphologic-metabolic biomarkers from [18F]FDG-PET/CT. The combination of SUVmax and CT-volume performed best. Based on these preliminary data, future prospective studies to validate this combined morphologic-metabolic imaging biomarker for potential therapeutic decisions seem promising.
Keywords: NSCLC; PET/CT; volume; SUVmax; prognostic value